2023
DOI: 10.1177/22808000231187959
|View full text |Cite
|
Sign up to set email alerts
|

Novel selenium and/or copper substituted hydroxyapatite–gelatin–chitosan–eggshell membrane nanocomposite scaffolds for bone tissue engineering applications

Sara Ibrahim Korowash,
Nik SA Nik Sharifulden,
Doreya Mohamed Ibrahim
et al.

Abstract: Limitations with the majority of bone therapeutic treatments include low availability, ethical constraints and low biological compatibility. Although a number of choice materials have been exploited successfully, there has always been scope for improvement as well as development of the next-generation of materials. Herein, scaffolds – developed from gelatin, chitosan and eggshell membranes – were crosslinked using tannic acid, and further infused with selenium and/or copper substituted hydroxyapatite nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Some studies reported Se-HA for improving the physicochemical and biological properties of polymers using as bone substitutes, but few of them could be used for load-bearing bone repair [26][27][28][29]. And no reports study the complex of Se-HA and PAA as load-bearing bone substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported Se-HA for improving the physicochemical and biological properties of polymers using as bone substitutes, but few of them could be used for load-bearing bone repair [26][27][28][29]. And no reports study the complex of Se-HA and PAA as load-bearing bone substitutes.…”
Section: Introductionmentioning
confidence: 99%